Students Learning Difficulties In Online Learning On One Variable Linear Equation Materials - Ofler Paulus Kodongan; Jorry F. Monoarfa; Derel F. Kaunang (Pusat Riset dan Inovasi Nasional, 2023)
The background of this research was found in students of SMP N II Tondano Class VII E who had learning difficulties in learning mathematics on one variable linear equation material through an online learning system. These problems make researchers interested in studying this research further. This study aims to determine the difficulties experienced by students in learning mathematics in PLSV material through an online learning system. This type of research is qualitative research. The data was obtained by giving a story problem description test and conducting student interviews. The research instrument was to provide the story and several interview questions for students online. The study results show that in learning mathematics in PLSV material through an online learning system, students experience difficulties memorizing equation formulas, and arithmetic operations, changing questions into mathematical forms, and difficulties understanding the material provided by the teacher. These problems are caused by 1) lack of interest and motivation in student learning, 2) not having a severe attitude in participating in online learning, 3) student concentration does not focus on learning material